The Right for a Healthy Environment in Indonesia: Comparison of Global Laws - Sigit Sapto Nugroho; Sarjiyati Sarjiyati; Anik Tri Haryani; Yuni Purwati; Susiani Tri Wahyuningsh; khudzaifah dimyati; Heru Santoso Wahito Nugroho (Journal of Global Pharma Technology, 2020)
Objective: The research purpose is to explains according the constitution every citizen has the right to obtain the constitutional guarantee to live and access the healthy environment. Method: The research methods is normative juridical method is conducted by examining literature material. Citizens also have the right to live in a good and healthy living environment for their growth and development. This is regulated in Article 28 on the Declaration of the Human Rights, the Stockholm Declaration, and the constitutions of countries in the international world. Results: Result of the research is the rights for a good and healthy environment brings a burden of responsibility for the state to protect and to sustain the living environment’s supporting power for the sake of the future generations. Conclusion: The conclusion from this research is that the efforts to uphold these rights may be guaranteed by the constitution. Thus, every citizen may file a lawsuit to the court if the state does not fulfil this right